Analysis of the Status and Prospects for the Introduction of Distance Learning at a Vocational School - Savchenko, Yurii (Pedagogical Discourse, 2013)
The article shows one of the possible schemes of the educational process at a vocational school. The state and prospects for implementation of distance learning were analyzed on the base of this scheme by example teaching Railroad professions «Mechanic on repairing of rolling stock II-III category», «The driver of the locomotive on diesel traction. The driver of the locomotive on electric traction». It is concluded that using the form of distance learning in the educational process at a vocational school would increase motivation of students and give them more opportunities to acquire a profession.